Metabolic Phenotyping of Atherosclerotic Plaques Reveals Latent Associations between Free Cholesterol and Ceramide Metabolism in Atherogenesis. - Vorkas,PA; Shalhoub,J; Isaac,G; Want,EJ; Nicholson,JK; Holmes,E; Davies,AH (Journal of Proteome Research, 2015)
Current optimum medical treatments have had limited success in the primary prevention of cardiovascular events, underscoring the need for new pharmaceutical targets and enhanced understanding of mechanistic metabolic dysregulation. Here, we use a combination of novel metabolic profiling methodologies, based on ultra-performance liquid chromatography coupled to mass spectrometry (UPLC-MS) followed by chemometric modeling, data integration, and pathway mapping, to create a systems-level metabolic atlas of atherogenesis. We apply this workflow to compare arterial tissue incorporating plaque lesions to intimal thickening tissue (immediate preplaque stage). We find changes in several metabolite species consistent with well-established pathways in atherosclerosis, such as the cholesterol, purine, pyrimidine, and ceramide pathways. We then illustrate differential levels of previously unassociated lipids to atherogenesis, namely, phosphatidylethanolamine-ceramides (t-test p-values: 3.8 × 10(-6) to 9.8 × 10(-12)). Most importantly, these molecules appear to be interfacing two pathways recognized for their involvement in atherosclerosis: ceramide and cholesterol. Furthermore, we show that β-oxidation intermediates (i.e., acylcarnitines) manifest a pattern indicating truncation of the process and overall dysregulation of fatty acid metabolism and mitochondrial dysfunction. We develop a metabolic framework that offers the ability to map significant statistical associations between detected biomarkers. These dysregulated molecules and consequent pathway modulations may provide novel targets for pharmacotherapeutic intervention.